An investigation into the effects of, and interaction between, heel height and shoe upper stiffness on plantar pressure and comfort. (2nd January 2019) - Melvin, Jonathan M.A.; Price, Carina; Preece, Stephen; Nester, Christopher; Howard, David
Abstract : High heeled shoes remain popular; nevertheless it is not clear what influence manipulating characteristics of this footwear has on their functioning. It is accepted that shoe features other than heel height can affect plantar pressures. However, few investigations have compared such features, and none have compared the influence of modifying upper material stiffness, whilst systematically increasing heel height. A firm understanding of the interactions of footwear properties is essential to ensure that footwear designers can optimise design for the comfort and health of the wearer. This paper investigates a feature that is known to reduce comfort (heel height) and a feature that is easy to change without affecting aesthetics (material stiffness) to better understand the effects of their interaction on plantar pressure and comfort. Sixteen female participants with experience wearing high heels wore a range of shoes with five effective heel heights (35–75 mm) and two upper materials (with different stiffness). In-shoe plantar pressure was recorded and participants completed a comfort questionnaire. Increasing heel height increased plantar pressure under the metatarsal heads, while reducing pressure in the hallux and heel. Higher heel heights also lead to increased discomfort, particularly in the toes where discomfort increased 154.3% from the 35 to 75 mm heels. Upper stiffness did not affect plantar pressure. However, stiffer uppers significantly increased reported discomfort, most notably on top of the foot (108.6%), the back of the heel (87.7%), the overall width (99%) and the overall comfort (100.7%). Significant interaction effects between heel height and upper material existed for comfort questionnaire data. Manipulating heel height alters plantar pressure and comfort, and choice of upper material is paramount to achieving wearer comfort in heels.